Development of Genome-Wide Functional Markers Using Draft Genome Assembly of Guava (Psidium guajava L.) cv. Allahabad Safeda to Expedite Molecular Breeding - Thakur, Sujata; Yadav, Inderjit Singh; Jindal, Manish; Sharma, Parva Kumar; Dhillon, Guriqbal Singh; Boora, Rajbir Singh; Arora, Naresh Kumar; Gill, Manav Indra Singh; Chhuneja, Parveen; Mittal, Amandeep (Frontiers in Plant Science, 2021)
Guava (Psidium guajava L.), a rich source of nutrients, is an important tropical and sub-tropical fruit of the family Myrtaceae and exhibits magnificent diversity. Genetic diversity analysis is the first step towards identifying parents for hybridization, genetic mapping, and molecular breeding in any crop species. Diversity analysis based on whole-genome functional markers increases the chances to identify the genetic associations with agronomically important traits. So, here we sequenced guava cv. Allahabad Safeda’s genome on Illumina platform and generated a draft assembly of ~304 MB. Allahabad Safeda genome assembly constituted >37.95% repeat sequences, gene prediction with RNA-seq data as evidence identified 14115 genes and BLAST n/r, Interproscan, PfamScan, BLAST2GO, KEGG annotated 13957 genes. Comparative protein transcript analysis of tree species revealed guava’s close relatedness with Eucalyptus. Comparative transcriptomics based SSR/InDel/SNP-PCR ready genome-wide markers in greenish-yellow skinned & white fleshed -Allahabad Safeda to four contrasting cultivars viz. apple color skinned & white fleshed -Lalima, greenish-yellow skinned & pink fleshed -Punjab Pink, purple-black skinned & purple fleshed -Purple Local and a widely used rootstock -Lucknow-49 were developed. Molecular markers developed here revealed a high level of individual heterozygosity level within genotypes in 22 phenotypically diverse guava cultivars. Principal coordinate, STRUCTURE clustering, and Neighbour-joining based genetic diversity analysis identified distinct clusters associated with fruit skin and flesh color. The genome sequencing of guava, functional annotation, comparative transcriptomics-based genome-wide markers, and genetic diversity analysis will expand our knowledge about genomes of climacteric fruits, facilitating trait-based molecular breeding and diversifying our nutritional basket.